Experimental Investigation on Rcc by Using Multiple Admixtures - P.Venkatreddy, Professor; Siva Krishna, A; SwamyYadav, G (International Journal of Engineering & Technology, 2018)
In this article, the effect of replacing cement with silica fume and fine aggregate with copper slag has been investigated. For this research work, concrete of M40 grade is prepared and evaluated for fresh and harden concrete properties such as compressive strength, tensile strength and flexural strength. Further, the cement is replaced with silica fume at 0, 2, 4, 6, 8 and 10 % and fine aggregate replaced with copper slag at 0, 10, 20, 30, 40 and 50 %. Compressive strength, strength and Flexure strength have been tested. It is observed from the results that the use of silica fume and copper slag as partial replacement material improves mechanical properties of the concrete. Concrete with 40 % copper slag and 8 % silica fume shows better performance among all the mixes.Â Â